HUBUNGAN PENILAIAN KINERJA PRAKTIKUM DENGAN ASPEK KEMAMPUAN METAKOGNITIF SISWA MTS NEGERI 1 LAMPUNG TIMUR - Susilohadi, Eko (Lembaga Penelitian UM Metro, 2019)
The purpose of this study are: (1) applying performance appraisal in the aspect of metacognitive ability of learners in solving biological problem. (2) knowing constraints assessing performance on metacognitive abilities. (3) knowing teacher's and students' feedback on performance appraisal. (4) knowing the limitations of performance appraisal in assessing metacognitive ability. In this study using the affordable population, the students of class 8A MTsN 1 Lampung East. As for the sample in this study all students of grade 8A MTsN 1 Lampung Timur. The data analysis techniques that will be used to test the hypothesis in this study is to use parametric inferential statistics, using multiple regression analysis techniques (Multiple Regression). Prior to testing hypothesis, then testing normality and homogeneity of data as a prerequisite for data analysis. Based on the results of data analysis and discussion it can be concluded as follows: (1) Metacognitive ability associated with cognitive activity. Metacognitive knowledge is concerned with declarative, procedural, and conditional knowledge. In order for a person to use his thinking skills through self-control, self-monitoring and evaluating a particular task, this is very important in solving the problem. (2) The constraints assess the performance of aspects of metacognitive ability ie long time and relatively complex judgments. (3) The response of teachers and learners about metacognitive ability is both good and significant in the teaching and learning process such as helping the problem solve effectively and helping to formulate the right concept. (4) The limitation of performance in metacognitive aspect is in the process of practicum because it involves knowledge and awareness of students about its own cognitive activity or anything related to its cognitive activity.